High Tensile Ductility and Strength in Bulk Nanostructured Nickel - Zhao, Yonghao; Topping, Troy; Bingert, John F.; Thornton, Jeremy J.; Dangelewicz, Andrea M.; Li, Ying; Liu, Wei; Zhu, Yuntian; Zhou, Yizhang; Lavernia, Enrique J. (Advanced materials (Weinheim), 2008)
Both high tensile ductility and high strength are achieved in bulk multimodal (Multi‐Ni) and bimodal (Bi‐Ni) nanostructured nickel, synthesized by cryomilling and subsequent quasi‐isostatic forging processes. The relatively low tensile ductility of bulk nanostructured materials has been a major obstacle for their practical applications. This work provides a new approach for fabricating bulk nanostructured materials with both high ductility and strength.